A 3-D Approach to Discovering and Creating the Features of Written Texts. (8th February 2016) - Pennington, Martha
Abstract : This article outlines a student-centered, 'hands-on' approach to the teaching of writing at university level through first discovering and then creating the features of written texts in three dimensions: microtextual (lexico-grammar), macrotextual (rhetoric), and extratextual (context). The '3-D' approach has been designed for novice writers, offering a practical, step-by-step procedure to prepare them to write in specific disciplines and for specific purposes. Though usable with other audiences, the sample material included here is especially appropriate for second-language writers and will be of particular interest to students of science. While the approach is consistent with Systemic-Functional and ESP orientations to text, as contrasted with most ESP pedagogy – especially that geared to students in sciences – the 3-D approach gives particular attention to affect, writer–reader interaction, and shared context. The approach, which starts from analysis of texts and then moves to writing of texts, is first described and then illustrated using several short popular science texts about insects and birds. These texts exemplify lexico-grammatical and rhetorical features of scientific texts while also illustrating other purposes which a writer may seek to fulfill as well as the underlying assumptions and author biases that might exist even in texts which appear to be purely descriptive or 'objective'. The texts and analyses provided are intended for classroom use to train students in the approach, supplemented by a step by step guide for students to follow. Through the activities provided for the sample texts, students develop awareness of the properties of texts and how these can be discovered through analysis and then written into their own texts.